Iron Depletion in the Deep Chlorophyll Maximum: Mesoscale Eddies as Natural Iron Fertilization Experiments. Issue 12 (28th November 2021) - Hawco, Nicholas J.; Barone, Benedetto; Church, Matthew J.; Babcock‐Adams, Lydia; Repeta, Daniel J.; Wear, Emma K.; Foreman, Rhea K.; Björkman, Karin M.; Bent, Shavonna; Van Mooy, Benjamin A. S.; Sheyn, Uri; DeLong, Edward F.; et al.
Abstract: In stratified oligotrophic waters, phytoplankton communities forming the deep chlorophyll maximum (DCM) are isolated from atmospheric iron sources above and remineralized iron sources below. Reduced supply leads to a minimum in dissolved iron (dFe) near 100 m, but it is unclear if iron limits growth at the DCM. Here, we propose that natural iron addition events occur regularly with the passage of mesoscale eddies, which alter the supply of dFe and other nutrients relative to the availability of light, and can be used to test for iron limitation at the DCM. This framework is applied to two eddies sampled in the North Pacific Subtropical Gyre. Observations in an anticyclonic eddy center indicated downwelling of iron‐rich surface waters, leading to increased dFe at the DCM but no increase in productivity. In contrast, uplift of isopycnals within a cyclonic eddy center increased supply of both nitrate and dFe to the DCM, and led to dominance of picoeukaryotic phytoplankton. Iron addition experiments did not increase productivity in either eddy, but significant enhancement of leucine incorporation in the light was observed in the cyclonic eddy, a potential indicator of iron stress among Prochlorococcus . Rapid cycling of siderophores and low dFe:nitrate uptake ratios also indicate that a portion of the microbial community was stressed by low iron. However, near‐complete nitrate drawdown in this eddy, which represents an extreme case in nutrient supply compared to nearby Hawaii Ocean Time‐series observations, suggests that recycling of dFe in oligotrophic ecosystems is sufficient to avoid iron limitation in the DCM under typical conditions. Key Points: Both cyclonic and anticyclonic eddies add iron to the lower euphotic zone of oligotrophic gyres In an anticyclonic eddy, dissolved iron at the deep chlorophyll maximum increased but productivity did not Uptake of upwelled iron and nitrate in a cyclonic eddy led to low iron conditions and stress, but did not limit productivity